Emerging technologies in the development of metallic and bimetallic nanoparticles in the last decade: a scientometric analysis (2023)
The development of nanotechnology and nanomaterials has had an upward surge in recent years, not only because of the type of technology but also because of the unique properties and characteristics of nanomaterials. This growth motivated us to make an analysis of emerging technologies in the development of metallic, bimetallic, and metal-oxide nanoparticles covering a period of ten years, which have had a high impact on the development of different products applied to biomedicine, electronics, agriculture, energy, plastics, etc. This research found more than one and a half million scientific papers under the keyword ‘nanotechnology’ in the Scopus database. This article reports a scientometric analysis where aspects such as articles with the highest number of citations, countries with the highest production, representative institutions in the field, authors and the relation of citations, correlations between them, keyword analysis, as well as the most studied topics in this field were investigated. On the other hand, the number of patents produced was reviewed in a general way. The databases Scopus, Journal Citation Report, VOSviewer, and other computer tools were used for the analysis. The results showed the United States (17.3%) and China (15.3%) as the countries with the greatest impact on studying metallic and bimetallic nanoparticles, with a high correlation between different countries. It is worth highlighting the participation of India with 10.1% and more than twice as many scientific papers as Germany; in the case of patents, the United States and China accounted for 55.3% of the total patents.